Avaliação de funcionalidade de escolares com síndrome de Down - Ramos, Elaine Cristina de Oliveira (2017)
Speaking of School Inclusion of children who have Intellectual Disability (ID) nowadays generates anxiety in schools, in educators and in the families. Schools, understood as a live and dynamic organism, should essentially develop the individual’s potentialities, competences and abilities, which demands that the teacher should recognize and identify the functionality of the student with the intellectual disability. This way, a plan of individual development can be elaborated for this student along with the family, which will effectively contribute to their academic and functional development. This research had the general aim of evaluating the functionality of students who have Down Syndrome and are enrolled in public and private regular schools of a region in the city of São Paulo. It also had as specific aims to evaluate the functionality of school children who have Down Syndrome from the perspective of parents or tutors and their teachers, and, at last, evaluate the degree of congruence between the perspectives of functionality reported by parents and by teachers of those children. Concerning methodology, the researcher conducted a survey of families who were eligible to participate in the project and, for that, analyzed the medical reports of the children being cared by the ISRAELI Center of Multidisciplinary Service (CIAM), in a way that she could identify children who were eligible to the study, according to inclusion criteria. She collected data about parents’ and tutors’ education in order to present the academic profile of the participant families. She got in touch with the families to introduce the research and applied the PAEDI protocol (Miccas and D’Antino,2011) with the parents or tutors, while the child was being attended by the CIAM. The questionnaire was read by the researcher, aiming at minimizing the differences that education could reflect in the reading interpretation and comprehension of the questions. She called schools and teachers to invite them to participate in the research and explain its objectives. She also sent the protocol - PAEDI (Miccas and D’Antino,2011) to teachers so that the questionnaires were answered and sent back to the researcher. The elaboration of this protocol had as basis the International Classification of Functionality, Disability and Health (CIF,2001) and it’s composed of 52 items. PAEDI evaluates the functionality of the child in the domains of Activities and Participation. As result of this research, it is clear that that there is congruence between families and school in a moderate level. The perceptions of each observer can be different and, although they are divergent and little congruent, the positive aspects are offered in the sense that different environments and informers allow different perspectives and offer varied information on the same child. PAEDI proved to be an important instrument of evaluation of the functionality of students who have intellectual disability.